2014
DOI: 10.1128/mcb.01473-13
|View full text |Cite|
|
Sign up to set email alerts
|

Isp7 Is a Novel Regulator of Amino Acid Uptake in the TOR Signaling Pathway

Abstract: c TOR proteins reside in two distinct complexes, TOR complexes 1 and 2 (TORC1 and TORC2), that are central for the regulation of cellular growth, proliferation, and survival. TOR is also the target for the immunosuppressive and anticancer drug rapamycin. In Schizosaccharomyces pombe, disruption of the TSC complex, mutations in which can lead to the tuberous sclerosis syndrome in humans, results in a rapamycin-sensitive phenotype under poor nitrogen conditions. We show here that the sensitivity to rapamycin is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 65 publications
(125 reference statements)
3
36
0
2
Order By: Relevance
“…Isp7 is a member of the family of 2-oxoglutarate-Fe(II)-dependent oxygenases. Isp7 regulates amino acid uptake through transcription regulation of general and specific amino acid permeases ( 27 ). The transcript of isp7 + is strongly upregulated following inactivation of TORC1 or in response to nitrogen stress (complete withdrawal of nitrogen from the growth medium or its replacement with a poor nitrogen source) ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isp7 is a member of the family of 2-oxoglutarate-Fe(II)-dependent oxygenases. Isp7 regulates amino acid uptake through transcription regulation of general and specific amino acid permeases ( 27 ). The transcript of isp7 + is strongly upregulated following inactivation of TORC1 or in response to nitrogen stress (complete withdrawal of nitrogen from the growth medium or its replacement with a poor nitrogen source) ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…Isp7 regulates amino acid uptake through transcription regulation of general and specific amino acid permeases ( 27 ). The transcript of isp7 + is strongly upregulated following inactivation of TORC1 or in response to nitrogen stress (complete withdrawal of nitrogen from the growth medium or its replacement with a poor nitrogen source) ( 27 ). However, isp7 + suppresses the induction of many nitrogen stress-induced genes, similarly to TORC1 ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pombe is not sensitive to rapamycin (Otsubo and Yamamato, 2008; Figure 2A). However, to eliminate competition from the endogenous TOR signalling system, we used a strain with a deletion of fkh1 + (eliminating the native FKBP12 domain) and combined this with tor1-S1834E (tor1SE) (Laor et al, 2014;Weisman et al, 2005). Mutation of the conserved serine (S) residue in the FRB domain of Tor1 to glutamic acid (E) residue dramatically reduces the interaction with Fkh1 in the presence of rapamycin (Weisman et al, 2005).…”
Section: Construction Of the Anchor-away Strainsmentioning
confidence: 99%
“…In S. pombe, five isp genes (isp3-isp7) were identified and they were preferentially expressed during sporogensis. Further study revealed that they were involved in diverse biological/biochemical functions (Yanagida, 2009;Shimanuki et al, 2010;Laor et al, 2014). Isp4 has been found up-regulated by nitrogen starvationinduced meiosis and found to encode an oligopeptide transporter (OPT).…”
Section: Introductionmentioning
confidence: 99%